Environmental performance of meranti sawmilling in Peninsular Malaysia - Ramasamy, Geetha (2015)
The sawmilling sector generates a large amount of wood waste and consequently,discharges several gases as a result of the resources consumption in the sawmilling activity. Therefore, the general objective of this study was to evaluate the environmental profile of the sawmilling activity in Malaysia, with particular reference to the sawing of Light Red and Dark Red Meranti (Shorea spp.) wood species. Meanwhile, the specific objectives were to measure the resources consumption, quantify the environmental burdens and evaluate the potential environmental impacts of the sawmilling activity. The resources consumption, environmental burdens and potential environmental impacts were compared against the test factors which were the wood species and the two different sawmills. The environmental performance of the sawmilling activity was evaluated using life cycle assessment (LCA) analytical tool. The methodological framework of LCA consists of four phases: goal and scope definition, life cycle inventory, life cycle impact assessment and life cycle interpretation. Two sawmills, known in this study as sawmill A and sawmill B were chosen for this study. Sawmill A, is the largest mill in Peninsular Malaysia, was set out as the base scenario of environmental performance assessment study. The inclusion of a corresponding medium-sized sawmill B, was to observe the differences in the environmental performance compared to sawmill A. The scope of the study was a gateto- gate measurement, which began once the saw logs entered the mill gate for the cutting process, until the production of rough green sawn timber. The data on material and energy consumption was collected on a monthly basis throughout the year 2013, in both sawmills. The environmental burdens were then quantified on the basis of the activity data and emission factors. The results of the study were divided into four parts. The first part of the study enumerated the recovery, in which it was found that the recovery of rough green sawn timber was higher for Light Red Meranti, while Dark Red Meranti generated higher amounts of wood losses in the form of splinters, sawdust and shavings for both sawmills. The chosen allocation was sawn timber as the main and the only product. The factorial ANOVA test showed significant difference in sawn timber recovery between the wood species, but not for sawmills and the interaction of sawmills and wood species. Saw logs characteristics (diameter and length), removal of defects and generation of wood residues were among the factors that affected the sawn timber recovery. Meanwhile, the similarity in machining parameters resulted in the non-significant differences between the sawmills, and also between the interaction of sawmills and wood species. The examination on the energy consumption identified,that electrical energy and diesel fuel energy were consumed higher for the Dark Red Meranti wood species. As a result, the emissions of CO2, CH4, N2O, SO2, NOx and CO were also higher for this wood species. The non-significant finding from the MANOVA and Mann-Whitney U tests is attributable to the comparable machining parameters and energy consumption. The study was continued to translate the environmental loads into potential environmental impacts. The results obtained were the global warming potential (CO2, CH4 and N2O), acidification potential (NO2 and SO2), human toxicity potential (NO2 and SO2), photo-oxidant formation potential (NO2 and SO2, CH4 and CO) and eutrophication potential (NO and NO2). The MANOVA analysis on the potential environmental impacts showed no significant differences between the sawmills, wood species and the interaction of sawmills and wood species,respectively. The results obtained were mostly likely associated with the environmental burdens assessment. Overall, the components depicted a positive and strong relationship with the potential environmental impacts. A comparative study of the potential environmental impacts showed global warming potential had the highest influence on the environment. A comparison of global warming potential has far reading implications on the sawmilling industry in the country. This study recommends further environmental performance studies on other tropical hardwood wood species and forest plantation wood species used in the sawmilling sector. Besides, further research on sawmilling with kiln drying facilities is also suggested.